Characterizing the cancer preventative properties of rosemary extract - Van Steenberg, Julia Elizabeth, author; Kato, Takamitsu, advisor; Legare, Marie, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2020)
Flavonoids have been established as antioxidants, with some demonstrating tumor suppression abilities; however, there has been little investigation into their abilities as selectively toxic agents, particularly in cancer cell lines. This investigation was carried out on three different cell lines: V79 a Chinese hamster lung cell, V-C8 a Breast Cancer type 2 (BRCA2) susceptibility protein mutant of V79, and a gene corrected variant of V-C8 containing the human chromosomes with intact BRCA2 gene. The latter two were used as off target cell lines to ensure only the BRCA2 deficient cells were negatively impacted and that intact human BRCA2 would be spared as well. A rosemary extract provided by Gifu University in Japan was tested for any potential cancer prevention abilities in BRCA2 deficient cell lines of breast cancer, due to inhibition of poly (ADP-ribose) polymerase (PARP) in the aforementioned three cell lines. Additional qualities of the rosemary extract were done in vitro using both the extract as a whole and the four known compounds within the extract, including the primary compounds of carnosic acid and carnosol. The four compounds were tested in pure form to better understand what part of the extract was causing any selective toxicity observed. Using mammalian cell culture, we were able to prove selective cell toxicity of BRCA2 deficient cells in comparison to the two off target cell lines. Further investigation revealed that rosemary extract acted as a PARP inhibitor, a quality that is associated with synthetic cell lethality in BRCA2 deficient cells. Finally the antioxidant capability of this mixture was quantified against a known antioxidant, ascorbic acid. Although rosemary extract as a whole does possess some minor antioxidant capabilities, it is capable of some level of hydrogen donation at sub LD50 concentrations in healthy cells. Antioxidants, in particular ascorbic acid, has shown evidence of improving quality of life, survival rate, and decreasing the overall initial risk of developing breast cancer. While there is not presently data in living systems, there is promise that due to selective cell toxicity and antioxidant abilities our rosemary extract will be able to act preventively against cancer developing in BRCA2 deficient cells.
Keywords: flavonoid; BRCA2; PARP